Industrial Needs on English Skills of New Employees: A Survey - Fikri Asih Wigati; Rianita Puspa Sari; Made Panji Teguh Santosa (STKIP Siliwangi, 2020)
Employees with good English skills tend to have greater opportunities to get better positions in their careers. Practitioners must consider workforce trends by conducting need analysis to explore how language is used in the workplace. This is important because learning English as a General Basic Course must be aligned with the needs of stakeholders. Karawang is the largest industrial city in Indonesia, the need for employees will certainly continue to increase. The main task of a university is to prepare its students to be ready to work and to have the skills needed by stakeholders. This study aims to identify the industry's need for English competence for employee recruitment from the perspective of corporate HRD both at the company level and at the Industrial area level. This research uses a quantitative approach with multilevel modelling methods. The research process is divided into four stages, namely the preliminary stage, the design of a theoretical framework, data collection and processing, the stage of analysis and drawing conclusions. The results of this research indicate that the ability most needed is the ability to actively communicate both speaking and writing. Reading and terminology mastery are equally important, but all four skills must be integrated in digital knowledge and online code analysis.information already present in the title. Keywords: Need Analysis, English Competencies, Employee Recruitment, Industry